Case Study of Nawarddeken Academy: On Country Learning in West Arnhem Land - Ober, Robyn (Australian and International Journal of Rural Education, 2024)
In 2023, researchers from the Batchelor Institute worked with staff, students and families from the Nawarddeken Academy in West Arnhem Land, which offers bicultural, community-driven education. Together, they engaged in a series of yarning circles as interviews with staff, students and families. The focus of the study was on retention, attendance and impacts from major events such as COVID-19. Nawarddeken Academy has a long history of fighting for educational rights for their children to learn on country, through an Aboriginal-led, controlled and managed model. This fight has spanned 20 years and today Bininj (Aboriginal) people are proud to provide education to their children on their land through Learning on Country programs that embed both-ways Bininj and Balanda (Aboriginal and non-Indigenous) knowledge/s into the school’s core curriculum. This article tells the story of Nawarddeken Academy and the case study research that was conducted with the school.